EFEK TELEDENTISTRY TERHADAP PENGETAHUAN SISWA SEKOLAH DASAR TENTANG DIET YANG BENAR UNTUK KESEHATAN GIGI - fildzah nurul fajrin; Haria Fitri; Nila Kasuma; Reno Wiska Wulandari; Wulandani Liza Putri (Universitas Baiturrahmah, 2022)
Introduction: Diet is one of the factors that influence the process of caries. Knowledge and understanding of diet patterns are needed from an early age to prevent caries. The Covid-19 pandemic hinders face-to-face education, but this can be overcome virtually through teledentistry. This study aimed to determine the level of knowledge of dental health in elementary school-age children on good dietary habits to prevent cavities through education teledentistry. Method: This cross-sectional analytic study was conducted on 61 3rd grade SD Kartika 1-11 Padang City students who met the inclusion and exclusion criteria. The purposive sampling technique made the selection of respondents. Education is done virtually with an online meeting application. Students' knowledge was measured using a questionnaire consisting of 13 closed questions which were given a value of 1 if the answer was correct and a value of 0 if the answer was incorrect. The data were processed with SPSS statistical software. Result: The results showed a significant increase in the average knowledge of respondents at pre-test2,64 ±1,059 increased to 4,98 ± 0,643 (p < 0.04) at post-test. Based on the results of the treatment effectiveness test/gain score, the result is 0,47. The intervention given has moderate effectiveness. Conclusion: This study concludes that education through teledentistry effectively increases knowledge about dental and oral health in elementary school students.